PENGARUH TEKNIK REPEATED READING TERHADAP KEMAMPUAN READING FLUENCY PADA SISWA KELAS III SEKOLAH DASAR - Ila Nurlaila Hidayat (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2013)
This research was conducted with students of grade III elementary school who are not fluent in reading with the goal to improve their reading fluency. Having quasi-experimental approach with single subject randomized time series design. researcher give repeated reading technique for 12 days. Every measurement session has data in WPCM score (word correct per minute). Comparison between pre-test and post-test show the increasing score of WPCM for 15.79. Error frequency and self-correction are getting decreased while reading expression is getting improved as the treatment session have. Repeated reading technique can improve reading influency.